Productive diversification of small orange producers in two municipalities of Huasteca Potosina, Mexico - Cuevas-Reyes, Venancio; Ramírez-Gómez, Carlos Julián; Rangel-Quintos, Jaime; Espinoza-Campos, Arely; Jiménez-Muñoz, EDITH (Acta Universitaria, 2026)
This study analyzes the productive diversification of small-scale orange producers in Tampacán (G1) and Axtla de Terrazas (G2), Huasteca Potosina, Mexico. Area, diversification, and productive profile were evaluated through interviews with 54 producers and nonparametric analyses (Kruskal-Wallis, chi-square, and Spearman’s correlation). Producers own an average of 3 ha, allocating 2 ha to orange cultivation in hilly areas. Age was different (p < 0.05) between group 1 (G1, 58 years) and group 2 (G2, 42 years). 25% of G1 and 37.5% of G2 have diversified production: G1 focuses on staple crops, while G2 cultivates citrus, sugarcane, and coffee. A negative correlation was found between orange acreage and diversification index (rho = -0.287, p = 0.036). Producers with larger orange acreages reported less diversification. Implementing comprehensive strategies that consider productive diversification will contribute to improving orange production.